The Effect of USD/IDR Exchange Rate, Interest Rate, and World Oil Price To Jakarta Composite Index (JCI) - Ummu Salma Al-Azizah; Yusdi Daulay; Naufal Krisnanto (Universitas Muhammadiyah Prof. DR HAMKA., 2019)
This research aims to investigate effect of selected macroeconomic variables, i.e., USD/IDR exchange rate, interest rate, and world oil price to indonesia composite index at the indonesia stock exchange (IDX). This paper examine the direct effect of selected macroecomonic variable on Indonesia Composite Index. The study used time series data from the 2012-2017. By using an regression technique analysis, the result from showed that simultaneously the exchange rate, interest rate, and world oil price have a significant effect on Indonesia Composite Index. Partially, only the exchange rate has a significant effect on Indonesia Composite Index, interest rate and world oil price have no significant effect on Indonesia Composite Iindex. The amount of influece caused by the three variables is 58% and the rest is explained by other variables.